Thresholds and noise limitations of colour vision in dim light. (5th April 2017) - Kelber, Almut; Yovanovich, Carola; Olsson, Peter
Abstract : Colour discrimination is based on opponent photoreceptor interactions, and limited by receptor noise. In dim light, photon shot noise impairs colour vision, and in vertebrates, the absolute threshold of colour vision is set by dark noise in cones. Nocturnal insects (e.g. moths and nocturnal bees) and vertebrates lacking rods (geckos) have adaptations to reduce receptor noise and use chromatic vision even in very dim light. In contrast, vertebrates with duplex retinae use colour-blind rod vision when noisy cone signals become unreliable, and their transition from cone- to rod-based vision is marked by the Purkinje shift. Rod–cone interactions have not been shown to improve colour vision in dim light, but may contribute to colour vision in mesopic light intensities. Frogs and toads that have two types of rods use opponent signals from these rods to control phototaxis even at their visual threshold. However, for tasks such as prey or mate choice, their colour discrimination abilities fail at brighter light intensities, similar to other vertebrates, probably limited by the dark noise in cones. This article is part of the themed issue 'Vision in dim light'.